Pemberdayaan Masyarakat Desa Dalam Mendukung Pendidikan Dasar Berkualitas di Desa Pikatan - Khoiruzzaim Kurniawan; Muhammad Soni Amrulloh; Abu Zaeni; Andressa Muthi Latansa; Mega Dwi Susanti (LP3M IAIFA Kediri, 2026)
Basic education in rural areas still faces significant challenges related to low student literacy and numeracy skills, as well as minimal parental participation. This study aims to analyze the effectiveness of community empowerment through the